2019
DOI: 10.21577/0103-5053.20190008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of L-Ascorbic Acid in Milk by Ultra-High-Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry Analysis

Abstract: This study provides a fast, accurate and reproducible method for L-ascorbic acid (L-AA) determination in milk samples by ultra-high-performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). A small volume of a low toxicity organic solvent (ethanol) was used for degreasing and deproteinization steps. Ethylenediaminetetraacetic acid disodium salt (EDTA) and formic acid were used as stabilizing agents. The method was successfully validated in terms of linearity, limit of detection (LOD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Furthermore, Table 4 shows a comparison between the analytical performances of the method developed in the present study with other chromatographic methods used for the L‐AA determination in the different sample matrices. Overall, the accuracy of the proposed method (2.2%) is comparable to that obtained by other studies [19,23,31,32] and much better than that reported by Baenas et al [18] (12.2%), Min et al [33] (5.0%), Temova Rakuša et al [34] (4.5%), Uckoo et al [35] (4.46%) and Frenich et al [22] (8.7%). Besides, the retention time (0.41 min), LOD (0.3 µg L −1 ) and LOQ (1.0 µg L −1 ) values were much lower in this study than all those presented in Table 4.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, Table 4 shows a comparison between the analytical performances of the method developed in the present study with other chromatographic methods used for the L‐AA determination in the different sample matrices. Overall, the accuracy of the proposed method (2.2%) is comparable to that obtained by other studies [19,23,31,32] and much better than that reported by Baenas et al [18] (12.2%), Min et al [33] (5.0%), Temova Rakuša et al [34] (4.5%), Uckoo et al [35] (4.46%) and Frenich et al [22] (8.7%). Besides, the retention time (0.41 min), LOD (0.3 µg L −1 ) and LOQ (1.0 µg L −1 ) values were much lower in this study than all those presented in Table 4.…”
Section: Resultssupporting
confidence: 82%
“…Several analytical methods have been used for the analysis of L-AA, including spectrophotometric and potentiometric [17], and chromatographic [18] techniques. High-performance liquid chromatography (HPLC) and ultra-high-performance liquid chromatography (UHPLC) have been widely used for L-AA determination in different products, such as milk [19,20], vegetables and fruits [18,21,22], fruit beverages and pharmaceutical formulations [23]. Compared with HPLC, UHPLC shows higher sensitivity, efficiency and resolution; shorter time and cost of analysis; and lower solvent consumption [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Commercial CB materials generally contain more than 97% carbon element and the rest are hydrogen, oxygen, and sulfur. [3][4][5] The primary particles of CB exhibit a spherical form and show a tendency to agglomerate, because of van der Waals forces among the CB nanoparticles. So, altering the surface chemistry and energy of CB is necessary to improve the dispersion of this nanomaterial in matrix, that is, polymer matrix, mechanical, electrical, thermal, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[6][7][8][9] Different techniques have been made to modify through grafting functional groups on the CB surface including, oxidation, 4,7,10-14 using surfactants, 10,15 polymer grafting, 11 halogenation, 11 thiolation, 11 sulfonation, 11 plasma treatment, 6,16 thermal treatment, 6,17 and using silane coupling agents. 4,7,[11][12][13][14] The surface oxidation methods widely used to introduce oxygen-containing groups (such as hydroxyl, ketone, phenol, ether, and carboxylic acid) on the surface of CB to prepare it for subsequent modification by covalent, electrostatic, and hydrogen bonding interactions, and/or to reach better dispersion in the polar media. 3,4,[12][13][14][18][19][20][21] The commonly involved oxidizing reagents are nitric acid, [6][7][8]10,14,[22][23][24][25][26] the mixture of sulfuric and nitric acid, 4,13,20,21,…”
Section: Introductionmentioning
confidence: 99%